2012
DOI: 10.1038/nrrheum.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated atherosclerosis in patients with SLE—mechanisms and management

Abstract: Rapid-onset cardiovascular disease is a major concern for many patients suffering from SLE. Cardiovascular events are more frequent and occur much earlier in SLE patients compared to healthy controls. Traditional risk factors such as altered lipid levels, older age and smoking do not fully explain the increased risk of cardiovascular disease, strongly suggesting that autoimmunity contributes to accelerated atherosclerosis. Altered immune system function is recognized as the primary contributor to both the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(147 citation statements)
references
References 118 publications
4
138
1
4
Order By: Relevance
“…This is particularly interesting considering that SLE patients display premature atherosclerosis and are at high risk for cardiovascular disease complications, which cannot be explained by the traditional risk factors. 33 Thus, our data suggest that anti-IgE treatment could be considered as a therapeutic option for accelerated atherosclerosis in autoimmune diseases. sIgM -/-were fed an atherogenic diet for 6 or 8 weeks respectively.…”
Section: A] Newman-keuls [B] Unpaired T Test and [C-e] Unpaired T Tmentioning
confidence: 99%
“…This is particularly interesting considering that SLE patients display premature atherosclerosis and are at high risk for cardiovascular disease complications, which cannot be explained by the traditional risk factors. 33 Thus, our data suggest that anti-IgE treatment could be considered as a therapeutic option for accelerated atherosclerosis in autoimmune diseases. sIgM -/-were fed an atherogenic diet for 6 or 8 weeks respectively.…”
Section: A] Newman-keuls [B] Unpaired T Test and [C-e] Unpaired T Tmentioning
confidence: 99%
“…Available data suggest that young women with SLE are at a substantially increased risk of AMI, congestive heart failure, and cerebrovascular accidents [12][13][14]. If autoantibodies develop during the progress of CI and CVD, they can be amplified in patients with SLE due to their dysregulated immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated atherosclerotic diseases have been recognized as major causes of mortality in SLE. In the study of large case series of patients with SLE, 6-20% and 4-15% of deaths were due to cardiovascular disease (CVD) and cerebrovascular disease, respectively [12][13][14]. To estimate the onset risk of accelerated atherosclerosis in SLE patients, several markers have been introduced including C-reactive protein [15], lipoprotein (a) [16], homocysteine [17], inflammatory cytokines [18,19], yet the satisfactory results have not been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients with SLE have been found to develop autoantibodies against ApoAI, which have been associated with acute coronary syndromes. 9 The development of B-cell-targeting therapeutics for RA and SLE has gained a lot of attention in the past years. The first B-cell therapeutic agent that has been approved for clinical use in patients with RA is the anti-CD20 antibody (rituximab).…”
Section: Targeting B Cells In Atherosclerosis and Myocardial Infarctionmentioning
confidence: 99%
“…There are also other autoantigens involved, such as heat shock protein 60,6,7 and the impact of other autoimmune diseases in promoting atherosclerosis such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) is well known. 8,9 The role of T cells and interferon-γ-secreting Th1 cells, in particular, as key drivers of plaque inflammation is well documented, and experimental approaches to dampen these responses by enhancing the activity of regulatory T cells are being tested. More recently, it was found that B cells could…”
Section: Immunity and Atherosclerosismentioning
confidence: 99%